A Quality of Life Guide for a Rural Purview in District Larkana Expending the GIS Evaluation in Hepatitis Exploration - Abbasi, Naila Parveen (Annals of Human and Social Sciences, 2024)
Hepatitis is a serious health issue in rural areas of District Larkana, as socioeconomic and environmental conditions, of hepatitis sufferer’s who significantly declined the quality of life. Main tasks covered the evaluation of wellbeing-associated social factors for way of life of hepatitis patients, also pinpointed the important symptoms. To evaluate HRQoL, a ground survey were carried out. The hospital registrants and interviewees were all approached through questionnaire for a study that is based on patient demographics and disease-related characteristics in the research area by the help of disease mapping using Geoinformatics techniques. The outcomes clearly shown, the lack of awareness and financial means are the reasons of poor quality of life of patients as most of belong to labor class who lived in villages under the joint family system were dissatisfied by way of their quality of life it came to know about the signs of a viral illness, such as hepatitis-related joint pain, exhaustion, fever, and anxiety, vomiting. Set the constant intensive care also monitoring system for disease related factors that can be helpful in supervision of situation in study area.